The Determinants of Ethical Principle Implementation in Nursing - Ni Putu Emy Darmayanti; Hanny Handiyani; Kuntarti Kuntarti (Journal of Health Sciences and Medicine, 2017)
The determinant of nursing ethics practice is not identified yet. This problem affects the ethical behavior of nurses in performing nursing care. According to that, it was influencing satisfaction and patient well-being. This study aims to identify the determinants of the ethical principles application in nursing. Descriptive, correlation, cross-sectional design was applied, through simple random sampling to 120 nurses. Data collecting used questionnaires, with univariate, bivariate, and multivariate analyzes. Determinants of nursing ethic application principle were job characteristics, nurses knowledge related to nursing ethics, supervision by supervisor, relationship with colleagues, awards, the role of head nurse, and tenure (p = <0,001-0,049). The most dominant variable was job characteristics (p <0,001). These factors need an attention by hospital manager to keep evaluating the other factors in order to improve the application of ethical principles in nursing.